DEVELOPMENT OF A SOLAR COLLECTOR USING RECYCLED FLUORESCENT LAMPS (Revista de Ciências Agroveterinárias, 2005)
The adoption of solar collector to water heating is limited in Brazil. The objective of this research was to develop an alternative solar collector to water heating using recycled fluorescent lamps. The collector was evaluated measuring the daily evolution of water temperature from 8:00 a.m. to 6:00 p.m. The measurements were performed from February 12 to 16, July 12 to 15 and December 12 to 15 of 2001. The statistics studies consisted of regression analysis. The results showed that the solar collector presented high thermal yield, especially in days with low solar radiation. The water maximum temperature inside the collector occurred around 4:00 p.m. The maximum absolute temperature values were 51.5oC, 41.0oC and 55.0oC in February, July and December, respectively.
Keywords: Solar alternative collector; recycled materials; low cost.